(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2024)
This article examines the social adaptation process of non-Uzbek spouses marrying into Uzbek families. It explores the challenges faced, including language barriers, cultural differences, and societal expectations. The study highlights key strategies for successful adaptation, such as language acquisition, cultural learning, and building strong relationships with extended family members. It also emphasizes the importance of balancing cultural identities and the role of family and community support in facilitating integration. The article concludes that while adaptation can be challenging, with the right strategies and support, non-Uzbek spouses can successfully integrate into Uzbek families, enriching both their own experience and the cultural diversity of the family.